2010
DOI: 10.7589/0090-3558-46.3.896
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Type a Influenza Virus in Wild Avian Species Using Two Serologic Assays

Abstract: Serologic testing to detect antibodies to avian influenza (AI) virus has been an underused tool for the study of these viruses in wild bird populations, which traditionally has relied on virus isolation and reverse transcriptase-polymerase chain reaction (RT-PCR). In a preliminary study, a recently developed commercial blocking enzyme-linked immunosorbent assay (bELISA) had sensitivity and specificity estimates of 82% and 100%, respectively, for detection of antibodies to AI virus in multiple wild bird species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 12 publications
9
57
0
1
Order By: Relevance
“…Two studies have reported IAV antibody test results for wood ducks, and in both cases no antibodies were detected (Kocan et al, 1979;Brown et al, 2010). One of these studies only tested serum from three wood ducks using a blocking ELISA (Brown et al, 2010), and the other study did not report sample size, but sera were tested by the agar gel immunodiffusion assay, which has been shown to perform poorly in waterfowl species (Bahl et al, 1975;Brown et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have reported IAV antibody test results for wood ducks, and in both cases no antibodies were detected (Kocan et al, 1979;Brown et al, 2010). One of these studies only tested serum from three wood ducks using a blocking ELISA (Brown et al, 2010), and the other study did not report sample size, but sera were tested by the agar gel immunodiffusion assay, which has been shown to perform poorly in waterfowl species (Bahl et al, 1975;Brown et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One of these studies only tested serum from three wood ducks using a blocking ELISA (Brown et al, 2010), and the other study did not report sample size, but sera were tested by the agar gel immunodiffusion assay, which has been shown to perform poorly in waterfowl species (Bahl et al, 1975;Brown et al, 2009). Experimentally infected wood ducks have developed an antibody response that has been detected up to 21 days after exposure to IAVs (Brown et al, 2009;Costa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aliquots of banked gull serum were acquired from previous studies conducted at multiple locations in Massachusetts during autumn/ winter and in New Jersey during spring (Brown et al 2010). In both cases, birds were captured using a cannon net or net launcher (Clark et al 2014).…”
mentioning
confidence: 99%
“…The high frequency of detection of antibodies in adults implies that C. c. roselaari, like C. c. rufa, is susceptible to AIV, and individuals from both populations may have some degree of immunity to specific subtypes (Brown et al 2010). The lack of positive results for chicks suggests that C. c. roselaari did not encounter AIV at natal sites, and chicks did not appear to have maternally derived AIV antibodies.…”
mentioning
confidence: 90%